2007
DOI: 10.1007/s12149-007-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonionic intravenous contrast agent does not cause clinically significant artifacts to 18F-FDG PET/CT in patients with lung cancer

Abstract: 6.11% for aorta, 5.85% ± 4.99% for liver, 5.47% ± 6.81% for muscle, and 2.81% ± 3.05% for bone marrow, and those of SUV ave were 10.17% ± 9.00%, 10.51% ± 7.89%, 4.95% ± 3.89%, 5.66% ± 9.12%, and 2.49% ± 2.50%, respectively. The mean differences of SUV max between enhanced and nonenhanced PET/CT were 5.89% ± 3.92% for lung lesions (n = 41), 6.27% ± 3.79% for LNs (n = 76), and 3.55% ± 3.38% for metastatic lesions (n = 35), and those of SUV ave were 3.22% ± 3.01%, 2.86% ± 1.71%, and 2.33% ± 3.95%, respectively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Based on our analyses, we found the highest percentage difference in SUVmax and SUVmean values were about 10% and 26%, respectively. These values are in agreement with the previous phantom and patient based findings [5,14,16,17], which have concluded that these changes are found to be not clinically significant. In fact, two previous clinical studies also found even higher differences than ours, the percentage difference in SUVmax due to contrast as high as 27%, and categorised them as clinically insignificant [6,28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on our analyses, we found the highest percentage difference in SUVmax and SUVmean values were about 10% and 26%, respectively. These values are in agreement with the previous phantom and patient based findings [5,14,16,17], which have concluded that these changes are found to be not clinically significant. In fact, two previous clinical studies also found even higher differences than ours, the percentage difference in SUVmax due to contrast as high as 27%, and categorised them as clinically insignificant [6,28].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the clearance of an intravenous contrast media between the CT image acquisition and the PET scan could result into this attenuation artifact [15]. However, the subsequent effect of this image artifact on the PET SUV values may not be of consequence, as several studies have found that the changes are clinically insignificant [5,14,16,17]. Thus, the application of contrast media in PET/CT imaging is no longer a matter of debate [18].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in SUVmax within normal lung tissue between non-contrast-enhanced CT (NCCT) and contrast enhanced CT (CECT) have been published. In one report, the percent increase in SUVmax between NCCT and CECT ranged from 13.19%–15.23% (p< 0.001) [47]. In another report, the percent difference in SUVmax between NCCT and CECT was less than 0.01%, (not significantly different) [48].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects fasted for at least 4 hours before 18 F-FDG PET/CT, which was done as previously described [17,18]. 18 F-FDG PET/CT findings were evaluated in two ways.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, 18 F-FDG PET/CT findings were quantified using maximum standardized uptake value (SUVmax). SUV is defined as the amount of radioactivity released per 1 g of tissue divided by the amount of radioactivity administered per 1 kg of body weight [17,18]. SUVmax was measured for 10 rotators of the head and neck for each subject by setting the globular-shaped volume of interest (0.96 cm 3 ).…”
Section: Methodsmentioning
confidence: 99%